The Robogut: A Bioreactor Model of the Human Colon for Evaluation of Gut Microbial Community Ecology and Function. Issue 4 (24th April 2023) - Gianetto‐Hill, Connor M.; Vancuren, Sarah J.; Daisley, Brendan; Renwick, Simone; Wilde, Jacob; Schroeter, Kathleen; Daigneault, Michelle C.; Allen‐Vercoe, Emma
Abstract: The human colon is inhabited by a complex community of microbes. These microbes are integral to host health and physiology. Understanding how and when the microbiome causally influences host health will require microbiome models that can be tightly controlled and manipulated. While in vivo models are unrivalled in their ability to study host‐microbial interplay, in vitro models are gaining in popularity as methods to study the ecology and function of the gut microbiota, and benefit from tight controllability and reproducibility, as well as reduced ethical constraints. In this set of protocols, we describe the Robogut, a single‐stage bioreactor system designed to replicate the conditions of the distal human colon, to culture whole microbial communities derived from stool and/or colonic biopsy samples, with consideration of methods to create culture medium formulations and to build, run, and sample the bioreactor apparatus. Cleaning and maintenance of the bioreactor system are also described. © 2023 The Authors. Current Protocols published by Wiley Periodicals LLC. Basic Protocol 1 : Growth medium preparation Support Protocol 1 : Preparing medium supplements Basic Protocol 2 : Preparing the bioreactor vessels Support Protocol 2 : Making acid and base bottles Support Protocol 3 : Preparing the effluent bottles Support Protocol 4 : Making acid solution Support Protocol 5 : Making base solution Basic Protocol 3 : Preparing inoculum and inoculating bioreactors Alternate Protocol 1 : Preparing inoculum less than 0.5% (w/v) of vessel volume Alternate Protocol 2 : Preparing synthetic community aliquots and inoculation via the septum Alternate Protocol 3 : Preparing inoculum from a tissue sample Basic Protocol 4 : Sampling the bioreactor vessel Basic Protocol 5 : Harvesting bioreactor vessel contents at end of experiment Support Protocol 6 : Cleaning and sterilizing sampling needles Basic Protocol 6 : Cleaning the bioreactor vessel Support Protocol 7 : Cleaning bioreactor support bottles